Future skills for Industry 4.0 integration and innovative learning for continuing engineering education - Azofeifa, Jose Daniel; Rueda-Castro, Valentina; Camacho-Zuñiga, Claudia; Chans, Guillermo M.; Membrillo-Hernández, Jorge; Caratozzolo, Patricia (Frontiers in Education, 2024)
This research explores leveraging Industry 4.0 technologies and best practices to address the challenges faced by Continuing Engineering Education (CEE) in Higher Education, ensuring its sustainability and relevance. CEE is essential for engineers' continuous professional growth and adaptability, especially in an era marked by swift technological progress and changing job requirements. CEE must adapt to rapid technological advancements and evolving workforce demands. Nevertheless, traditional pedagogical methods often lag behind the needs of modern engineering professionals. Through a case study, this study aims to show how skills visualization allows the creation of comparisons between professional scenarios to enhance the effectiveness and efficiency of CEE programs. To achieve this goal, we utilized a platform based on the KSA taxonomy, which enables the visualization of skills and supports creating personalized and adaptive learning. Anticipated outcomes demonstrate how comparing skills across occupations can highlight areas for reskilling or upskilling. Finally, This study underscores the significance of Education 4.0 principles in shaping the future of CEE programs, emphasizing the crucial role of innovative learning approaches and technological integration in empowering the future engineering workforce in the Industry 4.0 era.